LIPYAKSARA: THE CREATION OF THEATER ART USING ARTAUD'S CRUEL THEATER STYLE - Dharma, A. M. Surya Chintya (Journal of Social Science, 2025)
Objective: Lipyaksara is the name of a book owned by Calonarang. Calonarang herself is a powerful and magical woman. The contents of the Calonarang book contain mantras about good and evil. The Lipyaksara book created a conflict between Calonarang and King Airlangga's party in order to control the book. Creating war and Calonarang lost the battle. The story was realized into a theater performance with the same title as the book, Lipyaksara. The novel by Cok Sawitri entitled "Manggali Kalki" became the object for creating texts and dramatic performances. Method: Balinese traditional theater became the basis of the body in the process of realizing the work. The method of creating theater includes the process of adapting the novel into a performance text, training and exploring actors, to packaging it into an experimental performance. Results: So, Lipyaksara theater combines elements of Balinese tradition with an experimental modern theater style, creating a performance rich in narrative and artistic expression. Novelty: Worked using Artaud's Cruel Theater style.